Management of a Viable Ectopic Pregnancy on Caesarean Scar After IVF-ET Procedure: A Case Presentation - Kazım Gezginç; Rengin Karataylı; Dilay Gök; Ali Acar (Medical Network, 2012)
To present the management of a viable ectopic pregnancy on caesarean scar following IVF-ET procedure. A 33-year old woman with gravida 2, parity 1 admitted to our outpatient clinic in her 8th weeks of gestation. She had a previous caesarean section 4 years ago. Transabdominal ultrasound examination revealed empty uterine cavity and cervical canal, but an intramural viable gestation near the cesarean scar. Laparotomy was performed. The gestational sac was bulging and thinning out the uterine wall anteriorly at the scar site. We evacuated the products of conception and repaired scar. After 2 hours from the operation an abundant vaginal bleeding occurred and an emergent relaparatomy performed. No active bleeding focus could be detected but bilateral uterine arteries were ligated. As a result, caesarean scar pregnancy is a highly complicated type of ectopic pregnancy and should be kept in mind during routine obstetric practice.